Why do people participate in app-based environment-focused citizen science projects? - Etter, Simon; Strobl, Barbara; Seibert, Jan; van Meerveld, H. J. (Ilja); Niebert, Kai; Stepenuck, Kristine F. (Frontiers in Environmental Science, 2023)
We investigated the motivations of participants in two environment-focused citizen science projects using an online questionnaire. The questions focused on the reasons for initial engagement and in how far these motivations were fulfilled by participating. The two projects, CrowdWater and Naturkalender (English: Nature’s Calendar), use similar smartphone applications to collect data on water and phenology, respectively. The answers to the individual statements were analysed based on the categorization framework of Batson et al. (2002). The motivations to participate in the projects were similar for the two projects but there were also some differences. They were altruistic and related to participants’ principles (e.g., to uphold a moral principle, such as through conservation). The main motivations for becoming engaged in the projects were to contribute to science, due to an interest in the project topic, and to protect nature. More CrowdWater respondents were motivated by being asked to participate than Naturkalender respondents. Naturkalender participants and participants in the 50-59-year age group of both projects agreed most to enjoying their participation, being outside and active, and learning something new. More super-users, i.e., users who participated at least once per week, were interested in sharing their knowledge and experience with others than occasional participants. This was particularly true for super-users in Naturkalender. Based on the results of this study, we recommend that to help sustain involvement of the most active participants, projects should focus on recruiting participants who are already interested in the topic, and highlighting opportunities to share knowledge, be outdoors, and contribute to science.